TALAK DI LUAR PENGADILAN DAN IMPLIKASINYA - Khairizzaman; Armia (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2022)
Divorces outside the court are widely practiced by the community. Considering that this model of divorce is not officially recorded in state administrative law, it will have implications for other civil laws. This research is a normative research using descriptive analysis method. The results of the study show that divorce outside the court is a divorce that is carried out by the community unofficially and is not recorded based on the laws and regulations in force in Indonesia. In the perspective of Islamic law, this model of divorce is in principle valid as long as the terms and conditions of divorce law are fulfilled. Even so, this model of divorce from the perspective of positive law in Indonesia is considered invalid and the divorce agreement is deemed to have never existed, because it is not registered in state administrative law. The implications of divorce out of court include; the termination of the marriage bond, but both of them cannot obtain an official divorce certificate, also has an impact on civil rights to property law, the right to care for children, and cannot sue for matters that are binding under state law, uncertainty and has no permanent legal force.